2000
DOI: 10.1136/jech.54.11.864
|View full text |Cite
|
Sign up to set email alerts
|

The health of the Roma people: a review of the published literature

Abstract: Background-The Roma people originated in northern India and have been known in Europe for nearly a thousand years. For much of that time they have been the subjects of discrimination and oppression, culminating in the extermination of half a million Roma in the Nazi death camps. While it is widely believed that the health of Roma people is often poorer than the majority population, these inequalities remain largely unresearched. Methods-Published literature on the health of the Roma people was identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
190
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(204 citation statements)
references
References 26 publications
4
190
0
5
Order By: Relevance
“…Results from published literature on Roma health in Central Europe show several differences between the Roma population and the general population. Among the Roma higher birth and fertility rates are found, but also higher death rates, earlier start of reproductive activity and longer reproduction period, lower life expectancy and higher rates of illness [36][37][38] . The Roma population is also disadvantaged by lower education levels and greater illiteracy, which represent a major barrier to successful involvement in the labour market 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from published literature on Roma health in Central Europe show several differences between the Roma population and the general population. Among the Roma higher birth and fertility rates are found, but also higher death rates, earlier start of reproductive activity and longer reproduction period, lower life expectancy and higher rates of illness [36][37][38] . The Roma population is also disadvantaged by lower education levels and greater illiteracy, which represent a major barrier to successful involvement in the labour market 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It has furthermore been argued that unemployment may be a health hazard, and many studies have shown that unemployed persons have poorer health and higher mortality than employed people. It is generally recognised that those who are unemployed have lower quality of life and probably worse health and shorter life, particularly for males [36][37][38][39] . For this study, socioeconomic indicators were chosen from official statistics available in the Slovak Republic on the district level.…”
Section: Introductionmentioning
confidence: 99%
“…Rosicova et al (2011) found Roma ethnicity as a predictor of regional infant mortality rate in Slovakia. This is likely to contribute to the poorer CHD outcomes among Roma (Ginter 1998;McKee 1997;Hajioff and McKee 2000), but evidence on this is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This figure was mainly based on settled communities that the census could reach. The real number of Roma residents in Poland is probably higher, as illustrated in review published in 2000 [8]. The Roma ethnic group is the largest minority in several central and eastern European countries, comprising approximately seven million people [7].…”
Section: Males (%) Females (%)mentioning
confidence: 99%